Copy from collection of: IML-Berlin, IV-7-B 9.210: 'Brotverteilung in Weimar 1923; verteilt wurde eine Spende aus der Sowjetunion' - Wilhelm, Max (1923)
Copy from collection of: IML-Berlin, IV-7-B 9.210: 'Brotverteilung in Weimar 1923; verteilt wurde eine Spende aus der Sowjetunion'.